2016
DOI: 10.4049/jimmunol.1600401
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Activating Chicken Ig-like Receptor Recognizing Avian Influenza Viruses

Abstract: Chicken Ig-like receptors (CHIRs) represent a multigene family encoded by the leukocyte receptor complex that encodes a variety of receptors that are subdivided into activating CHIR-A, inhibitory CHIR-B, and bifunctional CHIR-AB. Apart from CHIR-AB, which functions as an Fc receptor, CHIR ligands are unknown. In the current study, we used a panel of different BWZ.36 CHIR reporter cells to identify an interaction between specific CHIRs and avian influenza virus (AIV). The specificity of the CHIR-AIV interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The LILRA genes, including LILRA1–6 , play an important role in the immune system of humans [ 1 , 7 ]. In chicken, some genes of the Ig superfamily such as TREM, CD300, SIRP, chicken Ig-like receptors (CHIR)-A, CHIR-B, CHIR-AB homologs and chicken leukocyte immunoglobulin receptor (LIR) were identified using bioinformatics approaches that may be important role in immune responses to high and low avian influenza virus [ 4 , 19 , 20 , 21 ]. However, functional characterization of the activating group of these genes has not yet been carried out in avian species including chickens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LILRA genes, including LILRA1–6 , play an important role in the immune system of humans [ 1 , 7 ]. In chicken, some genes of the Ig superfamily such as TREM, CD300, SIRP, chicken Ig-like receptors (CHIR)-A, CHIR-B, CHIR-AB homologs and chicken leukocyte immunoglobulin receptor (LIR) were identified using bioinformatics approaches that may be important role in immune responses to high and low avian influenza virus [ 4 , 19 , 20 , 21 ]. However, functional characterization of the activating group of these genes has not yet been carried out in avian species including chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The leukocyte immunoglobulin-like receptor (LILR) family consists of members that play inhibitory or activating roles on the genes of the proteins involved with the immune system and expressed in several primary innate immune cells (monocyte/macrophages, dendritic cells and CD4 + /CD8 + T cells) [ 1 , 2 , 3 ] and cell lines (HEK293 T cells, MDCK cells, HL-60 cells, thymoma BWZ.36 cells, epithelial cells and T cells) [ 1 , 4 , 5 , 6 ]. The LILR genes are highly homologous in the sequence of the extracellular regions and different in their sequences of the intracellular regions [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the gene expression and polymorphisms of LILRBs have been reported to be associated with autoimmune and infectious diseases such as those caused by Salmonella [8], cytomegalovirus [9], and Mycobacterium tuberculosis [10], as well as rheumatoid arthritis [11], Alzheimer’s model [12], psoriatic arthritis [13], HIV/AIDS [14], and cancer [6]. Recently, some members of the Ig superfamily that may be involved in immune responses such as triggering receptor expressed on myeloid cells, cluster of differentiation 300, signal regulatory protein and chicken Ig-like receptors (CHIR)-A, CHIR-B, and CHIR-AB homologs were identified in chicken using bioinformatics approaches [15]. The studies of the chicken leukocyte immunoglobulin receptor (LIR) indicated that LIR genes are shown highly polymorphic locus harboring a variable number of CHIR genes and also play an important role in avian influenza infection in chicken [15].…”
Section: Introductionmentioning
confidence: 99%
“…Systemically, microbiota can induce instructive signals to non-mucosal antigen-presenting cells and by producing among others IL-15, TNFα and IFN, subsequently prime optimal splenic NK cell responses (Ganal et al, 2012). Since chicken NK cells have been shown to express TLRs (Kannaki et al, 2010) and NCRs (Straub et al, 2013, Jansen et al, 2016, the interactions between microbiota and NK cells probably follow similar routes to those in humans and mice.…”
Section: Discussionmentioning
confidence: 99%